Effect of changing requirements: A tracking mechanism for the analysis workflow - DATTA, Subhajit (Institutional Knowledge at Singapore Management University, 2006)
Managing the effects of changing requirements remains one of the greatest challenges of enterprise software development. The iterative and incremental model provides an expedient framework for addressing such concerns. This paper presents a set of metrics - Mutation Index, Component Set, Dependency Index - and a methodology to measure the effects of requirement changes in the analysis workflow from one iteration to another. Results from a sample case study are included to highlight a usage scenario. Future directions of our work based on this mechanism are also discussed.